Analysis Of Understanding The Enterpreneurial Spirit In Running A Business In Msmes Warkop Simbah Lorah Ngasem Kediri - FUADI, MOCH. ILHAM; Kusumaningtyas, Dian (Universitas Nusantara PGRI Kediri, 2025)
Research aim : optimize employee performance and make a significant contribution to the development of business strategies in the MSME sector, especially in fostering the entrepreneurial spirit of business actors. Design/Methode/Approach: Qualitative methods are used by researchers to obtain information from interviews with businesses, employees, and consumers of Warkop Simbah Lorah UMKM. Research Finding : As a result of the research, Warkop Simbah Lorah MSMEs face problems in understanding the entrepreneurial spirit when running a business. Small and medium-sized businesses (MSMEs) are seeing increased competition for creativity and innovation. By applying the entrepreneurial spirit, businesses encourage employees to have an entrepreneurial spirit to increase customer loyalty and create a positive cycle for business continuity. This research shows that the growth of MSMEs greatly affects the understanding of the entrepreneurial spirit in terms of optimizing employee performance at MSME Warkop Simbah Lorah. Theoretical contribution/Originality : this research can be a benchmark and provide recommendations for MSME actors to increase the spirit of entrepreneurship through the development of an entrepreneurial spirit that must be owned by business actors. Practitionel/Policy implication : This research is expected to help MSME owners by providing advice and information on how to develop leadership style skills that can increase understanding of the entrepreneurial spirit and improve employee quality. For readers, this research is expected to be a reference for those who want to start a business and face problems about the entrepreneurial spirit. Research limitation : This researcher is very short of information related to detailed data, because MSME actors do not store data regularly